Counseling on Orderly Traffic from an Early Age for PAUD Shalsabila Education Pekanbaru Students - Neri Puspita Sari; Yulia Setiani Yulia; Zaiyar Zaiyar; Silfia Rini Silfia; Nurhasanah Nurhasanah; Manisya Aprilia Aprilia (Institut Riset dan Publikasi Indonesia, 2022)
Pekanbaru City is a metropolitan city with a very dense traffic volume with a low level of discipline for road users. Violations of traffic signs often occur and a sense of care to comply with traffic regulations is still low, accidents often occur. As a result of undisciplined road users, it creates anxiety and worries about accidents. For this reason, it is necessary to conduct traffic safety education. Traffic counseling should be taught from an early age, where children are able to provide an understanding of good behavior in order to form a disciplined child character. The teaching method is adjusted to the age where the Shalsabila PAUD children are aged 2.5 - 5 years which is included in the category of Toddler and preschool age. The method used is made fun by telling stories, singing and playing. So they are very enthusiastic and happy. Most preschoolers begin to understand and can distinguish what can be done and what can't be done.